Myeloid-Derived Suppressor Cells in Tumors: From Mechanisms to Antigen Specificity and Microenvironmental Regulation - Yang, Yuhui; Li, Chunyan; Liu, Tao; Dai, Xiaofang; Bazhin, Alexandr V. (Frontiers in Immunology, 2020)
Among the various immunological and non-immunological tumor-promoting activities of myeloid-derived suppressor cells (MDSCs), the immunosuppressive capacity remains a key hallmark. Effort in the past decade has provided us with a clearer view of the suppressive nature of MDSCs. More suppressive pathways have been identified, and their targets have been expanded from T cells and natural killer (NK) cells to other immune cells. These novel mechanisms and targets have rendered MDSCs with versatility in suppressing both innate and adaptive immunity. On the other hand, a better understanding of regulation on their development and function is unveiled. This intricate regulatory network, consisting of tumor cells, stromal cells, soluble mediators and hostile physical conditions, reveals bi-directional crosstalk between MDSCs and tumor microenvironment. In this article, we will review available information on how MDSCs exert their immunosuppressive function and how they are regulated in tumor milieu. As MDSCs are a well-established obstacle to anti-tumor immunity, new insights in the potential synergistic combination of MDSCs-targeted therapy and immunotherapy will be discussed.